Variations on R-curves and traction-separation relations in DCB specimens loaded under end opening forces or pure moments. (15th May 2020) - Pappas, Georgios A.; Botsis, John
Abstract: In this work the differences in R-curve response and traction-separation relations due to a finite damage zone or large-scale bridging (LSB) in mode I fracture on double cantilever beams (DCB) were investigated under end opening forces (EOF) and pure moments (PM). To realize PM loading, a novel test-rig was designed, built and used to test adhesive joints with metallic substrates and unidirectional carbon fiber reinforced polymer (CFRP) specimens. In the adhesive joints, no pronounced difference was observed between the R-curves due to the two loading conditions. However, the experiments on the CFRP specimens showed important differences on both R-curve and traction separation relations due to LSB when comparing EOF and PM loading. These differences are attributed to the different curvature of the specimens' arms in EOF and PM allowing for longer bridging zone in the latter case. The increase in the energy release rates was 40% for the specimens subjected to PM with about four times higher maximum crack opening displacements at the steady state. Pertinent cohesive zone simulations predict the respone very well.